Valuing Waste, Transforming Cities - United Nations Economic; Social Commission for Asia; the Pacific (United Nations, 2016)
‘Valuing Waste, Transforming Cities’ provides guidance, lessons and recommendations on how to accomplish the paradigm shift from viewing waste as a problem to a valuable resource. It explores a low-cost, low-technology, community-based and decentralized waste-to-resource model called the ‘integrated resource recovery centre’. The publication articulates key lessons learned by ESCAP and its partners in establishing integrated resource recovery centres across cities in Asia and the Pacific since 2009. These lessons are grouped around four important areas for waste-to-resource initiatives: (i) partnerships; (ii) awareness raising and behaviour change; (iii) facilities management and operational performance; and (iv) replication and scaling up.